2018
DOI: 10.1038/s41598-018-29652-8
|View full text |Cite
|
Sign up to set email alerts
|

Directly Probing Light Absorption Enhancement of Single Hierarchical Structures with Engineered Surface Roughness

Abstract: Hierarchical nanostructures are ideal architectures to harvest solar energy. The understanding of light absorption in single hierarchical structures is emergently important and greatly helpful in enhancing multiscale optical phenomena and light management. However, due to the geometrical complexity of hierarchical architectures, theoretical and experimental studies of light absorption have faced significant challenges. Here, we directly quantify light absorption in single hierarchical structures for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Studying the nonlinear absorption (NLA) response has promising significance for the research and progress of high-performance nonlinear optical devices. Previous studies have reported that the micro-/nanostructures on the surface can enhance the light absorption ability of materials, which has far-reaching importance in exploring how the fs laser-induced structures impact the NLA properties of YSZ single crystals. In the abovementioned analysis, it is noticed that the mechanism of material removal is the inerratic lattice exfoliation with a low thermal effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the nonlinear absorption (NLA) response has promising significance for the research and progress of high-performance nonlinear optical devices. Previous studies have reported that the micro-/nanostructures on the surface can enhance the light absorption ability of materials, which has far-reaching importance in exploring how the fs laser-induced structures impact the NLA properties of YSZ single crystals. In the abovementioned analysis, it is noticed that the mechanism of material removal is the inerratic lattice exfoliation with a low thermal effect.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology in the above experiments demonstrates that the cracks will expand along with specific directions and form anisotropic final structures on three crystal planes of 47 which has far-reaching importance in exploring how the fs laser-induced structures impact the NLA properties of YSZ single crystals. In the abovementioned analysis, it is noticed that the mechanism of material removal is the inerratic lattice exfoliation with a low thermal effect.…”
Section: = C N T T Imentioning
confidence: 92%
“…and Raman thermometry, [22,23] near-field power-meter approach, [24][25][26] etc., cannot be used to measure the 1D system subjected to controllable bending deformation. As a matter of fact, due to the practical difficulty of measurement, the study of thermal transport in bent 1D materials is yet in theory, [27] and the experimental reports are rather scarce.…”
Section: Doi: 101002/pssa202100348mentioning
confidence: 99%
“…This is due to the fact that either simulations cannot be carried out (they can be done only in wellknown material systems as they require the knowledge of the energy dependence of the refractive index, which is experimentally unknown, e.g., in many for wurtzite III-V NWs), or they can lead to inexact results, as we discuss in this paper. In this frame, the optical absorption is defined as the fraction of incoming light that is not transmitted, reflected, or re-emitted after interacting with the NW (α = P abs /P in ), as is commonly done with this type of measurement [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Several quantitative methods to measure the optical absorption of single nanostructures (including NWs) [23][24][25][26][27] or even single molecules [28,29] have been developed, but since all of these have their limitations and often require complicated measurement schemes, measurements on single NWs often rely on PL excitation (PLE) or photocurrent measurements and are thus qualitative in nature [8,11]. In this work, we present a method for measuring the optical absorption of semiconductor NWs with very high sensitivity, and which can be applied in the full temperature range down from mK up to the maximum stable temperature of the measured material, at variance with other methods to measure absorption, that have to be applied at [25] or near room temperature [24,26]. As a proof of principle, we show measurements performed at 70 K and at room temperature (due to slight heating by the laser the actual temperature at the laser spot is estimated to be at most 70 K above the measurement temperature at room temperature, and at most 20 K for the 70-K measurement).…”
Section: Introductionmentioning
confidence: 99%